Voting in Māori Governance Entities - Bargh, Maria; Rata, Arama (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2020)
Internationally, declining voter turnout is a topic of considerable concern in many liberal democracies. In this article, we investigate whether these similar trends can be discerned in the voter turnout for Māori governance entities. We first explore some of the demographic contexts within which Māori governance entities operate with a specific focus on population, residence, and age. We then provide a detailed descriptive analysis of voting data from one particular entity: Te Rūnanga o Ngāti Awa, with whom we worked to understand how their elections inform their aspirations for continuing connectedness with tribal members. In the final section of the article, we present findings from an analysis of publicly available tribal voting data to see whether the trend of declining voter turnout is observable and whether online voting is shown to impact turnout.